Psoriasis limited to Becker nevus of the back. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2013)
Typing in PUBMED "Becker nevus and psoriasis" or "Becker's melanosis and psoriasis" we found only two papers related to our case. The first article (1) refers to a 10-year-old child presenting from birth on the left buttock Becker's nevus. At the age of 5 years an intensely itching psoriasiform plaque covered completely the surface of Becker nevus. The second article (2) refers to a young patient who developed guttate psoriasis after an episode of tonsillitis. Curiously psoriasis although affecting the entire skin surface spared only the surface occupied by Becker nevus. Both reports argue that the aberrant clone of cells constituting Becker nevus somehow interferes with the development of psoriasis, in the first case favoring its emergence, in the second inhibiting its development.